Pengaruh Biaya Lingkungan, Perputaran Modal Kerja dan Tangibility terhadap Kinerja Keuangan - Nafisah Awalia; Ratna Anggraini; Putri Haryani (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to analyze the effect of environmental costs, working capital turnover, and tangibility on financial performance. This study employed a quantitative research method with a population consisting of companies in the basic materials sector. The sample comprised 35 companies selected using the purposive sampling method. The data were analyzed using panel data regression with E-Views version 13. The results indicate that environmental costs and working capital turnover have no significant effect on financial performance. In contrast, tangibility has a negative and significant effect on financial performance. These findings suggest that environmental cost allocation and working capital management have not yet become the primary factors in improving the financial performance of basic materials companies, whereas a higher proportion of fixed assets tends to reduce financial performance.